Epidemiology and predictors of spinal injury in adult major trauma patients: European cohort study - Hasler, Rebecca M. (Springer-Verlag, 2011)
This is a European cohort study on predictors of spinal injury in adult (≥16 years) major trauma patients, using prospectively collected data of the Trauma Audit and Research Network from 1988 to 2009. Predictors for spinal fractures/dislocations or spinal cord injury were determined using univariate and multivariate logistic regression analysis. 250,584 patients were analysed. 24,000 patients (9.6%) sustained spinal fractures/dislocations alone and 4,489 (1.8%) sustained spinal cord injury with or without fractures/dislocations. Spinal injury patients had a median age of 44.5 years (IQR = 28.8–64.0) and Injury Severity Score of 9 (IQR = 4–17). 64.9% were male. 45% of patients suffered associated injuries to other body regions. Age <45 years (≥45 years OR 0.83–0.94), Glasgow Coma Score (GCS) 3–8 (OR 1.10, 95% CI 1.02–1.19), falls >2 m (OR 4.17, 95% CI 3.98–4.37), sports injuries (OR 2.79, 95% CI 2.41–3.23) and road traffic collisions (RTCs) (OR 1.91, 95% CI 1.83–2.00) were predictors for spinal fractures/dislocations. Age <45 years (≥45 years OR 0.78–0.90), male gender (female OR 0.78, 95% CI 0.72–0.85), GCS <15 (OR 1.36–1.93), associated chest injury (OR 1.10, 95% CI 1.01–1.20), sports injuries (OR 3.98, 95% CI 3.04–5.21), falls >2 m (OR 3.60, 95% CI 3.21–4.04), RTCs (OR 2.20, 95% CI 1.96–2.46) and shooting (OR 1.91, 95% CI 1.21–3.00) were predictors for spinal cord injury. Multilevel injury was found in 10.4% of fractures/dislocations and in 1.3% of cord injury patients. As spinal trauma occurred in >10% of major trauma patients, aggressive evaluation of the spine is warranted, especially, in males, patients <45 years, with a GCS <15, concomitant chest injury and/or dangerous injury mechanisms (falls >2 m, sports injuries, RTCs and shooting). Diagnostic imaging of the whole spine and a diligent search for associated injuries are substantial. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00586-011-1866-7) contains supplementary material, which is available to authorized users.